Ag–Ag2S Hybrid Nanoprisms: Structural versus Plasmonic Evolution - Shahjamali, Mohammad M. (2017)
Recently, Ag–Ag2S hybrid nanostructures have attracted a great deal of attention due to their enhanced chemical and thermal stability, in addition to their morphology- and composition-dependent tunable local surface plasmon resonances. Although Ag–Ag2S nanostructures can be synthesized via sulfidation of as-prepared anisotropic Ag nanoparticles, this process is poorly understood, often leading to materials with anomalous compositions, sizes, and shapes and, consequently, optical properties. In this work, we use theory and experiment to investigate the structural and plasmonic evolution of Ag–Ag2S nanoprisms during the sulfidation of Ag precursors. The previously observed red-shifted extinction of the Ag–Ag2S hybrid nanoprism as sulfidation occurs contradicts theoretical predictions, indicating that the reaction does not just occur at the prism tips as previously speculated. Our experiments show that sulfidation can induce either blue or red shifts in the extinction of the dipole plasmon mode, depending on reaction conditions. By elucidating the correlation with the final structure and morphology of the synthesized Ag–Ag2S nanoprisms, we find that, depending on the reaction conditions, sulfidation occurs on the prism tips and/or the (111) surfaces, leading to a core(Ag)–anisotropic shell(Ag2S) prism nanostructure. Additionally, we demonstrate that the direction of the shift in the dipole plasmon is a function of the relative amounts of Ag2S at the prism tips and Ag2S shell thickness around the prism.